2013
DOI: 10.5513/jcea01/14.3.1285
|View full text |Cite
|
Sign up to set email alerts
|

Callus Induction and Plant Regeneration in Punica Granatum L. ʻnanaʼ From Leaf Explants

Abstract: In this investigation, leaf explants of a local cultivar of dwarf pomegranate were placed on Murashige and Skoog (1962) (MS) medium supplemented with various concentrations of 6-benzyl adenin (BA) and naphthalene acetic acid (NAA) for callus induction. After 40 days, maximum callus induction was observed on a media containing 1 mg L -1 BA and 0.2 to 0.4 mg L -1 NAA. However, the highest callus growth was obtained on a medium containing 1 mg L -1 BA and 1 mg L -1 NAA. The highest number of shoots (7 shoots per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…Genetic similarity between P. granatum mother plant, derived callus (cotyledons and leaves) and regenerated shoots based on SSR markers between two pomegranate cultivars and attributed the cause to the difference in levels of internal PGRs in each cultivar. This finding was also corroborated by Bonyanpour and Khosh-Khui (2013) who reported that contrary results obtained in shoot induction response was caused by differences in cultivar and explant type. Different results were also obtained from other plant species as well (Khateeb, Bahar, Lahham, Schroeder, & Hussein, 2012;Baskaran, Moyo, & Van Staden, 2013).…”
Section: Callussupporting
confidence: 82%
See 1 more Smart Citation
“…Genetic similarity between P. granatum mother plant, derived callus (cotyledons and leaves) and regenerated shoots based on SSR markers between two pomegranate cultivars and attributed the cause to the difference in levels of internal PGRs in each cultivar. This finding was also corroborated by Bonyanpour and Khosh-Khui (2013) who reported that contrary results obtained in shoot induction response was caused by differences in cultivar and explant type. Different results were also obtained from other plant species as well (Khateeb, Bahar, Lahham, Schroeder, & Hussein, 2012;Baskaran, Moyo, & Van Staden, 2013).…”
Section: Callussupporting
confidence: 82%
“…PGRs are not only important in tissue culture of pomegranate but also in other plants as well. Studies have been done to identify the best hormone and hormonal levels for shoot and root induction as well as for callus formation in pomegranate and other plant species (Patil el al., 2011;Bonyanpour & Khosh-Khui, 2013;Kaji et al, 2013aKaji et al, , 2013bParmar, Kanwar, & Thakur, 2013;Geetha, Harathi, & Naidu, 2016;Guranna, Hosamani, Sathyanarayana, Hegde, & Hipparagi, 2017). In this study, it was found that the presence of cytokinins (BAP and KN) in the culture media significantly induced shoots on nodal explants.…”
Section: Mpmentioning
confidence: 51%
“…Fresh and healthy leaves were taken from pomegranate trees ( Punica granatum cultivar Hegazy), washed under running tap water, and sterilized with 30% NaClO 27 . The sterilized-leaves were soaked in 150 mg L −1 AsA and 100 mg citric acid for 20 min and washed with sterilized-water 28 . In a 195 mL jar, three sterile leaf pieces (1–1.5 cm) were transplanted into 30 mL of sterilized and solidified MS medium.…”
Section: Methodsmentioning
confidence: 99%